Medical Examination in the Commemoration of the 106th Anniversary of Mlangi Besar Muhammadiyah Branch, Sleman Yogyakarta: Medical Examination in the Commemoration of the 106th Anniversary of Mlangi Besar Muhammadiyah Branch, Sleman Yogyakarta - Novalina, Dhiah Novalina; Yuyun Nailufar (Jurnal Pengabdian kepada Masyarakat Cahaya Mandalika (Abdimandalika), 2022)
Dhiah Novalina1, Yuyun Nailufar2 1,2,3 Program Studi Teknologi Laboratorium Medis, Universitas ‘Aisyiyah Yogyakarta Coresponding Author: dhiah.novalina@unisayogya.ac.id Abstract: Degenerative disease is a medical term which means a disease that occurs as a result of the decline in cell function, from normal to abnormal. This degenerative disease occurs due to smoking, alcohol consumption, lack of physical activity, lack of consumption of fibrous foods, lack of energy-dense consumption and central obesity. There are many kinds of degenerative diseases, one of which is diabetes mellitus, hypertension, gout arthritis. Therefore, it is necessary to carry out health checks and education related to the variables used as indicators of degenerative diseases. The hope is that when these medical variables can be detected early, prevention can be done as early as possible for the emergence of degenerative diseases in the community around the Muhammadiyah Branch of Mlangi Besar, Sleman Yogyakarta. Based on the examination, the results obtained were that the results of the examination of the people who attended the activity 77.4% had normal blood pressure and the other 16.12% were classified as level 1 hypertension. Meanwhile, the blood sugar levels of the people who were present 64.51% had normal blood sugar levels 25.80% pre-diabetic and 0.06% diabetic. On uric acid examination, 0.1% had uric acid levels above normal, while 90.32% had normal uric acid levels. The results of blood pressure, blood sugar and uric acid examinations for the people who participated in the 106th Anniversary of the Muhammadiyah Mlangi Besar Branch were mostly good, need to be improved by providing education and regular health examinations.